2018
DOI: 10.5469/neuroint.2018.13.1.54
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic Post Endarterectomy Common Carotid Artery Pseudoaneurysm Treated with Combination of Flow Diverter Implantation and Carotid Stenting

Abstract: A 74-year-old male developed cervical carotid artery psuedoaneurysm 8 months after carotid endarterectomy. The patient was successfully managed with dual implantation of flow-diverter and conventional carotid stent. Flow-diverter was placed across the neck of pseudoaneurysm to provide flow diversion while carotid stent was implanted within the lumen of the expanded flow-diverter to approximate and hold the flow diverter proximal and distal to the pseudoaneurysm. Follow-up ultrasonography revealed complete reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…15) Likewise, a Flow-Diverter stent could not be used because it is not available in the size that would have been needed for this case. 17) In previous reports, overlapping bare metal stents have had good short-term results, but no long-term results have been reported until now. 19) Therefore, we decided that it was necessary to use a coil combination.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…15) Likewise, a Flow-Diverter stent could not be used because it is not available in the size that would have been needed for this case. 17) In previous reports, overlapping bare metal stents have had good short-term results, but no long-term results have been reported until now. 19) Therefore, we decided that it was necessary to use a coil combination.…”
Section: Discussionmentioning
confidence: 97%
“…Types of stents reported in the literature include covered stents, bare metal stents, and Flow-Diverter stents. [15][16][17] In situations where the vascular endothelium has failed, such as cases with dissection or a failed CEA, the endovascular approach with a metal stent is useful. 18) In this case, the continuity between the aneurysm and the common carotid artery was confirmed adventitia by MRI (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Carotid artery PEPA is a rare complication of CEA, reported to occur in about 0.3e0.6% of the procedures. 3 Although this complication can arise both after patch angioplasty and direct suture closure, some authors found it to be twice as common after patch angioplasty. 1 The factors that can lead to PEPA include suture line disruption, degeneration of the arterial wall or patch, infection, or even clamp/shunt induced damage.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Post-endarterectomy pseudoaneurysms (PEPA) are a rare complication of CEA that occur in about 0.3e0.6% of the procedures. 3 The aetiology includes suture line failure and degeneration of the arterial wall or of the patch. Additionally, some authors report this rare complication to be twice as common after patch angioplasty compared with primary closure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation